2009
DOI: 10.1177/1059840509347377
|View full text |Cite
|
Sign up to set email alerts
|

Defining, Delivering, and Documenting the Outcomes of Case Management by School Nurses

Abstract: Case management is a component of school nurse practice that provides an opportunity to demonstrate the contribution that school nurses make to the health and academic success of children, particularly children with chronic health conditions. However, case management programs vary in their mission and scope, leading to confusion about what it means to be a case manager. Many programs acknowledge the difficulty in tracking outcomes and sustaining results. Using a capacity-building approach, the Case Management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…Each of the categories associated with the substantive theory is discussed below. (Bonaiuto, 2007;Engelke et al, 2009;Lee, Mackenzie, Dudley-Brown, & Chin, 1998). Participants also did not discuss the health promotion roles of environmental management or advocacy that have been described by other researchers who have examined school nurse work in the US (Bednarz, 1998;Engelke et al, 2014;Wainwright, Thomas, & Jones, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of the categories associated with the substantive theory is discussed below. (Bonaiuto, 2007;Engelke et al, 2009;Lee, Mackenzie, Dudley-Brown, & Chin, 1998). Participants also did not discuss the health promotion roles of environmental management or advocacy that have been described by other researchers who have examined school nurse work in the US (Bednarz, 1998;Engelke et al, 2014;Wainwright, Thomas, & Jones, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It is based on a thorough assessment by the school nurse including input from the family and teachers. (Engelke, Guttu, & Warren, , p. 421)…”
Section: Introductionmentioning
confidence: 99%
“…In the world of nursing, the terms care coordination and case management have been used interchangeably (McClanahan & Weismuller, 2015). Furthermore, school nurse case management (SNCM) efforts have not been standardized and programs have varied in their scope and vision (Engelke et al, 2009). A closer look at case management, using a case management program exemplar, will help clarify how case management is used in the context of the Framework for 21st Century School Nursing Practice (NASN, 2016a).…”
Section: Case Managementmentioning
confidence: 99%
“…Through shared planning with the student and family, interventions—outlined in the student’s individualized healthcare plan (IHP)—are goal oriented and evaluated based on the health and academic needs of the child. Case management involves a system of care, such as the healthcare team, surveillance and tracking systems, evidence-based guidelines, and interagency partnerships (Baker et al, 2017; Case Management Society of America [CMSA], 2016; Engelke et al, 2009; NASN, 2016a).…”
Section: Case Managementmentioning
confidence: 99%
“…Although care transition is not discussed in the literature related to schools, several studies have looked at the broader structure of care coordination and case management of school nurses (Engelke, Guttu, & Warren, ; Engelke, Swanson, & Guttu, ; McClanahan & Weismuller, ). Engelke and colleagues found that when school nurses served as case managers to coordinate care, there were improved health and academic outcomes, as well as parent satisfaction and student quality of life.…”
mentioning
confidence: 99%